Single-Cell Analysis of the Neonatal Immune System Across the Gestational Age Continuum - Peterson, Laura S.; Hedou, Julien; Ganio, Edward A.; Stelzer, Ina A.; Feyaerts, Dorien; Harbert, Eliza; Adusumelli, Yamini; Ando, Kazuo; Tsai, Eileen S.; Tsai, Amy S.; Han, Xiaoyuan; Ringle, Megan; et al. (Frontiers in Immunology, 2021)
Although most causes of death and morbidity in premature infants are related to immune maladaptation, the premature immune system remains poorly understood. We provide a comprehensive single-cell depiction of the neonatal immune system at birth across the spectrum of viable gestational age (GA), ranging from 25 weeks to term. A mass cytometry immunoassay interrogated all major immune cell subsets, including signaling activity and responsiveness to stimulation. An elastic net model described the relationship between GA and immunome (R=0.85, p=8.75e-14), and unsupervised clustering highlighted previously unrecognized GA-dependent immune dynamics, including decreasing basal MAP-kinase/NFkB signaling in antigen presenting cells; increasing responsiveness of cytotoxic lymphocytes to interferon-a; and decreasing frequency of regulatory and invariant T cells, including NKT cells and MAIT cells. Knowledge gained from the analysis of the neonatal immune landscape across GA provides a mechanistic framework to understand the unique susceptibility of preterm infants to both hyper-inflammatory diseases and infections.